การพัฒนากระบวนการเรียนการสอนตามแนวคิดการถ่ายโยงการเรียนรู้และรูปแบบความเป็นไปได้ของการขยายความในการโน้มน้าวใจเพื่อส่งเสริมทักษะและเจตคติในการปฏิบัติการพยาบาลผู้สูงอายุสำหรับนักศึกษาพยาบาล - นาตยา รัตนอัมภา (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The objectives of this study were to 1) develop an instructional process based on transfer of learning approach and elaboration likelihood model of persuasion to promote nursing practice skills and attitude toward gerontological nursing for nursing students, and 2) to evaluate the effectiveness of an instructional process. The effects of using the develop instructional process by conducting a one group pre-test post-test quasi-experiment. Thirsty-six purposive samples of Mahidol University nursing students were selected. The duration of experimental was 12 weeks with research instruments, consist of The Health assessment report and nursing care plan evaluation, the systematic observation of gerontological nursing assessment and The attitude toward gerontological nursing evaluation questionaire. The data were analyzed by using t-test for comparing nursing practice skills and attitude toward gerontological nursing The result of this study were as follows: The instructional process develop with an aim to promote nursing practice skills and attitude toward gerontological nursing for nursing students was composed of nine principle; 1) motivate motivation and ability 2) assignment 3) data processing and knowledge structure building 4) application data 5) Transferring thinking strategy 6) group discussion 7) Ponder and reflection 8) evaluation and feedback 9) summarized idea. The teaching stage, consisting of 1) motivate motivation and ability 2) knowledge structure building and nursing care plan 3) nursing practice 4) Ponder and summarized idea. The results from application of the instructional process showed that after the experiment, the sample group had higher skills and attitude toward gerontological nursing scores at the significant level of .05 and overall mean scores of gerontological nursing practice skills increased overtime.